Implementation of National Values in Order to Build A Generation of Youth With Integrity through Basic Education for State Defense - Aliyah, Yurizki; Susmoro, Harjo; Patmi, Sri (Formosa Journal of Applied Sciences, 2024)
This study aims to analyze the implementation of national values in order to form a generation of youth with integrity through basic education for state defense. The research methods used are literature study and secondary data analysis. The results showed that the implementation of national values in basic education has influenced the attitudes and behaviors of the youth generation. The discussion revealed that through good basic education in defending the country, the youth generation can become agents of change who have integrity and love for the motherland. The conclusion of this study is the need to increase the implementation of national values in basic state defense education in order to form a generation of youth with integrity and character.